Lifelong learning for Malaysians through Geragogy - Mohd Salim, Mohd Nur Fitri; Nik Mat, Nik Mahfuzah; Amzah, Rodhiah; Mohamad Yusuf, Asmahanim; Mohd Salim, Mohamad Safwat Ashahri (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Malaysia’s rapidly ageing population—projected to reach one in seven people aged 60 and above by 2030—highlights the urgent need for adaptive lifelong education as seniors are expected to comprise 11.6% of the population in 2024 and 17% by 2040. As the country adapts to this demographic shift, geragogy becomes increasingly important as a specialised approach to teaching older adults, recognising their distinct motivations such as financial literacy, social reconnection, and personal development, as well as challenges including physical limitations, slower cognitive processing, and limited technological experience. By addressing these needs, geragogy ensures learning environments that are equitable, relevant, and respectful of seniors’ life experiences.